Miscue analysis of oral reading among non-proficient Malaysian ESL learners - Ramakrishna Pillai, Adeena Deepa; Paramasivam, Shamala (TechMind Research Society, 2014)
Reading is a vital skill. Research has shown that proficient learners usually have a greater comprehension of the reading material. This study focuses on non-proficient learners’ oral reading as a direct method of assessing their reading ability. Miscue analysis is used as a tool to gather information and measure strategies used in reading and comprehending a given material. The study investigates the types and frequencies of miscues made by learners when they orally read texts and assesses learners’ comprehension based on the oral reading through the use of multiple-choice questions. The number of miscues made and the scores for the multiple choice questions are patterned using Microsoft Excel program and are converted into percentages. This study found that when the number of miscues made by the learners reduced during the oral reading process, the scores on the comprehension section did not necessarily improve. The types of miscues made by learners were omission of words namely plural and past-tense endings of verbs, substitution of words such as the pronoun ‘she’ with ‘he’, and hesitation especially with complex words. The findings imply that learners have language problems in grammar, vocabulary, pronunciation, and the use of reading strategies.